Tourism/Migration. Terms of an Enantiomorphic Category - Migliore, Tiziana (E|C, 2022)
This article examines a relationship, which in the last decades has become increasingly recurrent, the one between tourism and migration. Under the complex macrocategory of mobility, two narrative programmes stand out about the couple tourism/migration: leaving home temporarily for pleasure, to enjoy a holiday, and leaving home permanently for duty, to work, to improve one’s social status or in order to escape from war, persecutions or cataclysms. While some political parties and press organs instrumentalise these differences, by enhancing the circulating stereotypes to give a positive vision of the tourist and a negative one of the migrant, the mobile condition of today, no longer as a sporadic fact but almost as a norm for individuals and groups, facilitates the associations and marks an intermediate form of life that we all persons share: wandering. Thus, tourism and migration, in many discourses and representations, appear to be the enantiomorphic image of each other, in the Lotmanian sense of dialogical mechanisms that are specularly equal, but unequal if they overlap: an ironic mirror of the paradoxes of the globalized world. A Banksy’s left-hand campervan and artistic tour in August 2021, satirizing on the government suggestion to domestic vacations, exposes tourism and migration as the flip side of each other’s coin. We will analyse the artistic video that Banksy posted after his way around on his Instagram page, A Great British Spraycation to see how this particular declination of the “street art” sheds light into the issue.